Prevalence and Associated-Factors for Entamoeba gingivalis in Adolescents in Southeastern Iran by Culture and PCR, 2017 - Maryam SHARIFI; Fatemeh JAHANIMOGHADAM; Zahra BABAEI; Mohammad Ali MOHAMMADI; Fatemeh SHARIFI; Nima HATAMI; Masumeh DANESH; Parnian POURESLAMI; Hamidreza POURESLAMI (Tehran University of Medical Sciences, 2020)
Background: This study aimed to identify the prevalence and potential factors associated with Entamoeba gingivalis in adolescents in the city of Kerman, southeastern Iran, 2017. Methods: In this descriptive cross-sectional study, 315 adolescents (mean age; 15 yr) consisting of 189 males and 126 females were randomly selected. For each adolescent, two specimens were collected for culturing and examination by polymerase chain reaction (PCR). Univariate and multivariate logistic regression models were performed to explore any association with demographic and clinical variables. Results: The prevalence of E. gingivalis was 11.7%. Totally, 30 (15.9%) males and 7 (5.6%) females were infected with E. gingivalis. The rate of infection in males was 2.8 times higher than that in females (P<0.001). Statistical analysis identified 4 major factors including sex (OR=4.12, P<0.001), gingival index with severe inflammation (OR = 50, P<0.001), Candida spp. infection (OR=4.41, P<0.001) and decay-missing- filled teeth [DMFT (OR=3.27, P<0.001)]. In contrast to the aforementioned factors, adolescents with history of antibiotic consumption were significantly protected from E. gingivalis infection (OR= 3.24, P<0.001). Culture media detected 9.2% (n= 29), whilst PCR identified 11.4% (n= 36) of infection. Conclusion: The present findings clearly demonstrate a positive association between E. gingivalis and distinct demographic and clinical risk determinants. Therefore, dental practitioners and health surveillance personnel should be aware of these confounding factors to rigorously detect and critically manage oral health issues in school-age children in order to prevent or at least minimize the eventual periodontal complications in later life.